The persistence of regional entrepreneurship: Are all types of self-employment equally important? - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2015)
We explore the role of different types of self-employment for a persistence of the regional level of entrepreneurship over time. Our analysis for West German regions shows relatively strong effects for the historical self- employment rate in the non-agricultural sector, particularly in knowledge- intensive industries on current levels of new business formation. While self-employment by males shows a statistically significant relationship, the self-employment rate of females remains statistically insignificant. Also, no statistically significant effect can be found for the share of homeworkers that can be regarded a rather weak form of entrepreneurship.
Keywords: L26; R11; O11; 330; entrepreneurship; entrepreneurship culture; new business formation; persistence; self-employment